Diagnostic Efficacy of Endometrial Aspiration Cytology in Abnormal Uterine Bleeding - A Cross Sectional Study at a Tertiary Care Hospital - Amita Kumari (Light House Polyclinic Mangalore, 2021)
Background: Application of cytology in evaluation of endometrial lesions is emerging and is a valuable diagnostic tool which includes endometrial aspiration cytology and imprint cytology. This study was conducted to analyze the morphological patterns of endometrium in abnormal uterine bleeding by endometrium aspiration cytology and to compare its diagnostic efficacy of with histopathology. Material and method: This was a prospective analytical study which included 127 cases with abnormal uterine bleeding. Aspiration was done using nasogastric tube. This was followed by dilatation and curettage, material obtained and serial imprints were taken. The endometrial biopsy was then sent for histopathological examination. The aspirates and biopsy were stained appropriately. Cytomorphology was studied and subsequently correlated with histopathological features. Results: Mean age was 41.57 Â± 8.42 years and menorrhagia was the most common pattern of bleeding. The most common endometrial pattern observed was of cyclic endometrium by both the techniques. The sensitivity, specificity, positive predictive value and negative predictive value of endometrial aspiration cytology in diagnosing malignancy was 66.67%, 100%, 100% and 99.07% respectively. Conclusion: Endometrial cytology is a simple, rapid, safe and cost-effective tool in evaluating abnormal uterine bleeding in identification of specific pathology. Pathologist must be aware of the cytomorphology and potential pitfalls especially in distinction of atypical hyperplasia and grade 1 adenocarcinomas to improve diagnostic accuracy.